Concordance of the facial biotype with the pattern of facial growth in women and men - Inda-Velázquez, Kenia Leticia (2019)
Objective: To determine if the fa cial biotype and the pattern of facial growth agree in women and men. The study universe was 673 lateral radiographs of skull pretreatment of orthodontics. The sample was 100 radiographs of which 50 were of each sex. The average age in women was 13.7 years and in men 17.08 years. Ricketts VERT and Jarabak's facial height ratio were performed. The data was captured on the electronic record sheet and descriptive statistics were performed in the Microsoft Excel program. The Kappa test was performed in the calculator in Excel for the Kappa-Fisterra Index and the Student t tests were performed in the SPSS 19 program. Results: the mesofacial facial biotype was found in women 48% and in men with 44% the dolichofacial biotype. The average of VERT was -0.356 in women and in men of -0.31. The growth pattern 65.28% in men and women of 62.25%. The result of the Kappa index between the two analyzes was 0.37 in women and 0.16 in men. When comparing the VERT values of men and women, no significant differences were found. In the growth pattern there were significant differences. The average of the VERT was mesofacial in both sexes. The growth pattern   was mesodivergent in women and hypodivergent in men. There is no relationship in the results of one method compared to the other. Significant statistical differences were found in the ratio of facial height between both sexes.